TURNING DISASTER INTO BUSINESS OPPORTUNITY THROUGH PROCESSING OF POTATO STICK IN SIOSAR VILLAGE KARO DISTRICT - Siahaan, Riana Friska; Mutiara, Erli (Universitas Negeri Medan, 2017)
AbstractThe purpose of this activity is to empower the potential owned by the partner community. The activities are conducted from July to November 2017. Activity partners are Ati Rohati and home industries Wahyuni. Location of activity in Suka Meriah Village Siosar Kec. Brand Kab. Karo. This village is an area where the relocation of people affected by eruption of Mount Sinabung. Located 110 km from Unimed. Methods of implementation of activities are education, production training, business management training, machine use and mentoring. Output t of this activity is 1) Potato Sticker Machine and 2) Potato Stick. Specifications of potato sticks are: 1) Have nutritional content: Carbohydrates, Proteins, fats, iron, and fiber; 2) Durable and hygienic. Results of activities obtained are partners have knowledge of potato stick processing, actively participating partners, skilled partners using potato sticker printing machine. Partner production is getting better and partner income is also increasing.Keywords: Stick, Potato, Disaster, Karo